1996
DOI: 10.1542/peds.97.4.486
|View full text |Cite
|
Sign up to set email alerts
|

Informing Subjects of Epidemiologic Study Results

Abstract: Objective. To assess the feasibility and process of providing feedback to parents regarding the results of epidemiologic research, in particular to look at the importance and clarity of the information provided, parental reactions to the results, and utilization of the data provided. Methodology. Parents who participated in an epidemiologic study of pediatric brain tumors (patient and control mothers) were sent a letter summarizing the results of the study and the Parent Study Results Survey to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In one study, >50% of parents of paediatric participants in a rheumatologic clinical trial reported increased interest in participating in subsequent research after receiving the results of the current trial in which their child was participating 5 . In another study, mothers of children with and without cancer acknowledged interest in participating in subsequent epidemiologic research after the return of study results 6 . Study participants have also expressed interest in learning study results even when there is no immediate or future personal benefit 7 …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In one study, >50% of parents of paediatric participants in a rheumatologic clinical trial reported increased interest in participating in subsequent research after receiving the results of the current trial in which their child was participating 5 . In another study, mothers of children with and without cancer acknowledged interest in participating in subsequent epidemiologic research after the return of study results 6 . Study participants have also expressed interest in learning study results even when there is no immediate or future personal benefit 7 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, communication of aggregate results through lay summaries is likely a feasible and necessary endeavour for public health, for which investigators have evaluated the acceptability and impact 11–13 . Prior studies have focused on lay summary distribution in the setting of life‐threatening illness or chronic disease, where traditional, randomized trials evaluate the safety and efficacy of targeted therapeutics 5,6,11,14 . Little is known about the provision of lay summaries outside these specific patient populations and study designs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations